2012
DOI: 10.1103/physrevlett.109.096602
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Switching of Perpendicularly Magnetized Magnetic Layers Using Spin Torque from the Spin Hall Effect

Abstract: We show that in a perpendicularly magnetized Pt/Co bilayer the spin-Hall effect (SHE) in Pt can produce a spin torque strong enough to efficiently rotate and switch the Co magnetization. We calculate the phase diagram of switching driven by this torque, finding quantitative agreement with experiments. When optimized, the SHE torque can enable memory and logic devices with similar critical currents and improved reliability compared to conventional spin-torque switching. We suggest that the SHE torque also affec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

88
1,445
10
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,564 publications
(1,546 citation statements)
references
References 37 publications
88
1,445
10
3
Order By: Relevance
“…Keeping this in mind, we now analysis the current induced magnetization switching by SOTs with the assistant of an in-plane x-directional magnetic field (H x ). We first consider the equilibrium equation of the magnetization using a simple macrospin model considering the external field torque, the anisotropy torque and the spin orbital torque [1,30,31]. When J e flowing along + direction, the SHE induced J s is generated perpendicular to the Co layer (along the direction from Pt layer and along the direction from Cr layer) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping this in mind, we now analysis the current induced magnetization switching by SOTs with the assistant of an in-plane x-directional magnetic field (H x ). We first consider the equilibrium equation of the magnetization using a simple macrospin model considering the external field torque, the anisotropy torque and the spin orbital torque [1,30,31]. When J e flowing along + direction, the SHE induced J s is generated perpendicular to the Co layer (along the direction from Pt layer and along the direction from Cr layer) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, current induced spin-orbit torques (SOTs) in trilayer structures, where ultrathin ferromagnets (FM) is sandwiched by a heavy metal (HM) and an oxide, have attracted abundant research interests for highly effective magnetization switching [1][2][3] and fast domain wall motion [4][5][6][7][8][9][10]. In such a SOT-based device, when an in-plane charge current (J e ) flows through HM with strong spin-orbit coupling (SOC) including 5d-metal Pt [2], Ta [11], W [12], and Hf [13], etc., it can be converted into a pure spin current (J s ).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] For the opposite effect, to use Pt as a spin current injector, a charge current is sent through the Pt, creating a transverse spin accumulation by the spin-Hall effect (SHE). [6][7][8] Recently, Weiler et al 9 and Huang et al 10 observed magnetoresistance (MR) effects in Pt on YIG and related those effects to magnetic proximity. These MR effects have been further investigated by Nakayama et al 11 and they found and explained a new magnetoresistance, called spin-Hall magnetoresistance (SMR).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional spin transfer torques (STTs), they do not need another ferromagnetic layer as a spin polarizer and the high driving current density does not need to cross the tunnel barrier 6,7 . However, there are many debates on the SO torque induced magnetization dynamics, for example, whether the spin Hall torque (SHT) from SHE 4,5 or Rashba effect 3 is the dominant source to induce the magnetic switching. Even for the basic magnetic switching mechanism, it is still not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Spin-orbit (SO) torques arising from the spin Hall effects (SHE) and Rashba effect have attracted considerable attentions recently because they provide an alternative way to switch magnetization as well as drive domain wall (DW) motions [1][2][3][4][5] . Compared with conventional spin transfer torques (STTs), they do not need another ferromagnetic layer as a spin polarizer and the high driving current density does not need to cross the tunnel barrier 6,7 .…”
Section: Introductionmentioning
confidence: 99%